Characterization of Synthesized Zeolite Socony Mobile 5 (ZSM-5) from Bularafa Diatomite. - Yunusa, S.; Ahmed, A. S.; Yusuf, M.; Bawa, S. G. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
In this study, a highly siliceous ZSM-5 zeolite with elemental silicon to aluminium ratio of 250 was synthesized using Bularafa diatomite as silica source. The diatomite was used to produce silica sol which was used with alumina in the presence of organic template (tetrapropyl ammonium bromide, TPABr) to form ZSM-5 under hydrothermal reaction at low temperature and atmospheric pressure in alkaline medium. The synthesized ZSM-5 was characterized using X-ray diffraction (XRD), Fourier transformation infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), N2 adsorption and X-ray fluorescence (XRF). The Brunauer, Emmet and Teller (BET) method revealed that the ZSM-5 produced from Bularafa diatomite have very high specific surface area of 619 m2 g–1.